Chromosome-level assembly of the Clinopodium gracile genome - Gao, Yubang (Frontiers in Plant Science, 2024)
Clinopodium gracile is an important medicinal herb in the Lamiaceae family. This species lacks corresponding genomic resources, which significantly limits the study of its active compound synthesis pathways, breeding practices, and assessment of natural genetic variations. We assembled the chromosomal-level genome of C. gracile using Oxford Nanopore (ONT) technology and Hi-C sequence. The assembled genome is 307.3 Mb in size and consists of 9 chromosomes. The scaffold N50 was 36.3 Mb. The BUSCO completeness (Embryophyta_db10) of the genome was 97.2%. The genome annotates 40,083 protein coding genes. C. gracile and S. miltiorrhiza diverged approximately 30.615 million years ago. C. gracile has not undergone recent species-specific WGD events. A high proportion of young LTRs indicates a recent transposable element (TE) transposition burst in C. gracile.